Jawabanmu

2014-05-04T15:30:41+07:00
8-3x = 17 -3x = 17-8 -3x = 9 x = 9รท(-3) x = -3
2014-05-04T15:31:13+07:00
Contoh seperi ini :
f(x +1) = 3x + 2 ---> f(x) = 3x - 1
(g o f)(x) = 9x^2 - 6x + 2.
g(f(x)) = 9x^2 - 6x + 2.
g(3x - 1) = 9x^2 - 6x + 2

Misal A = 3x - 1 --> x = (A + 1)/3

g(A) = 9(A + 1)/3)^2 - 6((A + 1)/3) + 2
.......= 9(A^2 + 2A + 1)/9 - 6(A + 1)/3 + 2
.......= A^2 + 2A + 1 - 2A - 2 + 2
.......= A^2 + 1

a. g(x) = x^2 + 1

b. (f o g)(-1) = f(g(-1)) = f(-1^2 + 1) = f(2) = 3(2) - 1 = 5